1999
DOI: 10.1002/pen.11599
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide assisted blending of polystyrene and poly(methyl methyacrylate)

Abstract: A method for blending polystyrene and poly(methyl methacrylate), (PMMA), with the addition of supercritical carbon dioxide has been investigated. The first series of blends was a PMMA and polystyrene with similar melt viscosities. The second series of blends was a PMMA and polystyrene with a viscosity ratio (ηPMMA/ηpolystyrene) of about 20. The results show that a reduction in the size of the minor or dispersed phase is achieved when supercritical carbon dioxide is added to the blend system. A high‐pressure mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 27 publications
2
43
0
1
Order By: Relevance
“…If the latter effect is more pronounced than the former, the capillary number can be sufficiently increased to surpass j c , thereby resulting in CO 2 -enhanced droplet breakup. Experimental evidence confirms [173][174][175][176][177] that scCO 2 can substantially decrease the dispersion size of various polymer blends by lowering the viscosity and/or reducing the interfacial tension. For instance, the addition of scCO 2 to an immiscible PMMA/PS blend with an initial viscosity ratio of ca.…”
Section: Polymer Blendingmentioning
confidence: 67%
See 1 more Smart Citation
“…If the latter effect is more pronounced than the former, the capillary number can be sufficiently increased to surpass j c , thereby resulting in CO 2 -enhanced droplet breakup. Experimental evidence confirms [173][174][175][176][177] that scCO 2 can substantially decrease the dispersion size of various polymer blends by lowering the viscosity and/or reducing the interfacial tension. For instance, the addition of scCO 2 to an immiscible PMMA/PS blend with an initial viscosity ratio of ca.…”
Section: Polymer Blendingmentioning
confidence: 67%
“…20 results in a significant reduction of the viscosity ratio, as well as the PMMA dispersion size. [173] In a comparable blend, an initial viscosity ratio of 7.3 is lowered to 3.4 upon addition of scCO 2 , and the dispersion size correspondingly decreases in both batch and continuous mixing processes. [176] Indeed, the dispersion size in a 25:75 (w/w) PMMA/PS blend systematically decreases with increasing CO 2 concentration, as illustrated by the sequence of TEM images displayed in Figure 10.…”
Section: Polymer Blendingmentioning
confidence: 98%
“…[46] In extrusion processes, exposure to CO 2 can facilitate intimate mixing of different polymers because of improved viscosity matching. [47][48][49][50][51] Polymer blends produced in this manner tend to exhibit finer dispersions and improved impact strength. The sorption of CO 2 in PMMA/PVDF blends, as well as the accompanying changes in blend properties, has been examined by Paul and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Shows effects blending of two polymers under supercritical CO 2 on the morphology of the product as seen under a transmission electron microscope (TEM). Elkovitch et al (1999). Figure 32.…”
mentioning
confidence: 99%
“…The monomer polymerizes in the matrix of the polymer, producing a new blend of polymers with different and improved physical and chemical properties that are difficult to synthesize by conventional methods, see Berens et al (1986). For example, Elkovitch, et al (1999) showed the effects of supercritical CO 2 on the blending of PMMA and polystyrene using both a batch mixer (with a single-screw extruder) and a continuous operation mixer (with a twin-screw extruder). Figure 31 shows the effects of SCF_CO 2 on the morphology of the final product.…”
mentioning
confidence: 99%